Versatile asymmetric thiophene/benzothiophene flanked diketopyrrolopyrrole polymers with ambipolar properties for OFETs and OSCs. Issue 36 (23rd August 2017) - Jiang, Zhaoyan; Ni, Zhenjie; Wang, Hanlin; Wang, Zhen; Zhang, Jianqi; Qiu, Gege; Fang, Jin; Zhang, Yajie; Dong, Huanli; Lu, Kun; Hu, Wenping; Wei, Zhixiang
Abstract : Three novel asymmetric flanking diketopyrrolopyrrole based polymers with different π bridges were applied to organic solar cells as a donor or an acceptor, respectively. Abstract : Three novel asymmetric thiophene/benzothiophene-flanked diketopyrrolopyrrole (DPP)-based polymers with different π bridges, designated as PBTTDPP-BT, PBTTDPP-TT and PBTTDPP-2FBT, were designed, synthesized and employed in organic solar cells. Compared with the reported thiophene/pyridine-flanked DPP, these thiophene/benzothiophene-flanked DPP polymers exhibited narrower band gaps below 1.5 eV, leading to a broadened absorption that ranged from 500 nm to 850 nm. All polymers displayed promising ambipolar semiconducting properties. PBTTDPP-BT, PBTTDPP-TT and PBTTDPP-2FBT showed hole mobilities of 1.20, 1.68 and 1.50 cm 2 V −1 s −1, respectively. Their corresponding electron mobilities were 0.40, 0.14 and 0.35 cm 2 V −1 s −1 . Interestingly, PBTTDPP-TT and PBTTDPP-2FBT also showed ambipolar properties in organic solar cells. Photovoltaic device based on PBTTDPP-TT as a donor material reached a power conversion efficiency (PCE) of 6.96% with PC71 BM as an acceptor, while this device as the acceptor material achieved only 0.28% with poly(3-hexylthiophene) (P3HT) as the donor. In contrast, PCE of PBTTDPP-2FBT-based devices reached 5.62% with PC71 BM and 0.44% with P3HT. These results suggest that the adoption of asymmetric flankers in DPP polymers can effectively tune their ambipolar transporting properties for high-performance organic electronic devices.